Preliminary Study on the Host Response to Bivalent and Monovalent Autogenous Vaccines against Mycoplasma agalactiae in Dairy Sheep - Hany A. Hussein; Marco Tolone; Lucia Condorelli; Paola Galluzzo; Roberto Puleio; Irene Vazzana; Maria Luisa Scatassa; Gavino Marogna; Santino Barreca; Guido Ruggero Loria; Lucia Galuppo; Sergio Migliore (Veterinary Sciences, 2022)
In Italy, dairy sheep farming represents a vital agro-industry sector, but it is still challenged by contagious agalactia (CA), which is endemic there, and vaccination is the most economical and sustainable tool for control. This study aimed to evaluate the combined Mycoplasma agalactiae (Ma)-Staphylococcus aureus (Sa) vaccine (Ma–Sa) against the Ma monovalent vaccine in ewes. Twelve primiparous Ma-free ewes were randomly grouped into three equal groups: first, the control group injected with placebo, second, the group vaccinated with the Ma monovalent vaccine, and third, the group vaccinated with Ma–Sa combined vaccine, with two S/C doses at 45-day intervals. The animals were examined for serological, hematological, and somatic cell count (SCC) changes for 17 successive weeks. A significant increase in anti-Ma antibody mean titers, leukocytes, and platelets was observed in the vaccinated animals, with the highest values in those who received the combined vaccine. Neutrophils were high only in the animals who received the combined vaccine. SCC was lower in the vaccinated animals during the first six weeks. This study concludes that the combined Ma–Sa vaccines enhance immune response and potentiate its efficacy against Ma. This improvement might be attributed to the sensitization/activation effect of S. aureus on platelets, which are recoded to act as a key regulator for the coordination of all components of the innate immune system. Even though this study included a small number of animals, its findings about the potentialities of this inactivated vaccine in the control of CA are strongly encouraging. Further confirmation might be needed through additional replicates and a challenge study is needed before proceeding with widespread use.